2007
DOI: 10.1002/clc.20145
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Filtration Rate and Coronary Artery Disease Burden in Patients with Acute Coronary Syndrome

Abstract: SummaryBackground: Mild renal dysfunction may be associated with increased cardiovascular morbidity and mortality.Methods: The relation between estimated glomerular filtration rate (eGFR), as calculated from plasma creatinine at admission, and coronary artery disease burden (CADB), was studied in a cohort of 110 patients with acute coronary syndrome and coronary atherosclerosis.Results: A relatively weak but significant negative correlation was found between eGFR and CADB as measured by angiography (coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…In the present study eGFR value in CAD patients differed significantly from that of patients with normal coronaries on CAG (80.8 ± 22.9, 91.3 ± 28.9, p < 0.001),CAD patients tend to have low eGFR (Table 2). In a study by Jos'e Pedro L et al [29], a relatively weak but significant negative correlation was found between eGFR and CAD burden on angiography (r = −0.26, p = 0.006), this is in agreement with the observed negative correlation of eGFR with CAD in present study (r = −0.148, p < 0.02) ( Table 3). World Journal of Cardiovascular Diseases Though the strength of correlation is small, the increase in the HbA1c, CIMT values and decrease in the glomerular filtration rate predicted CAD on angiography as explained by Spearman correlation analysis (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study eGFR value in CAD patients differed significantly from that of patients with normal coronaries on CAG (80.8 ± 22.9, 91.3 ± 28.9, p < 0.001),CAD patients tend to have low eGFR (Table 2). In a study by Jos'e Pedro L et al [29], a relatively weak but significant negative correlation was found between eGFR and CAD burden on angiography (r = −0.26, p = 0.006), this is in agreement with the observed negative correlation of eGFR with CAD in present study (r = −0.148, p < 0.02) ( Table 3). World Journal of Cardiovascular Diseases Though the strength of correlation is small, the increase in the HbA1c, CIMT values and decrease in the glomerular filtration rate predicted CAD on angiography as explained by Spearman correlation analysis (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…In a cohort previously studied, including 110 patients with acute coronary syndrome, relatively weak but significant correlations were seen between CADB and decreased renal function, on the one hand, and plasma calcium, on the other hand [2].…”
Section: Introductionmentioning
confidence: 91%
“…More recently, a decrease in renal function was also noted to be associated to coronary artery disease [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronary artery disease increases in prevalence with lower eGFR and is the leading cause of mortality in patients with CKD . Among patients referred for coronary angiography, those with CKD have a higher prevalence of severe coronary artery disease, often have significant coronary artery lesions amenable to angioplasty, and more frequently have high‐risk coronary anatomy, including left main or 3‐vessel coronary disease, compared to those without CKD . These observations suggest that coronary revascularization has the potential to improve outcomes of patients with CKD, including symptoms of coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%